SUFFERING, GUILT AND RESPONSIBILITY - Robert Neville (Journal of Dharma, 2020)
Suffering pervades human existence, and much of it seems un- avoidable. We suffer from the ill-will, weakness, thoughtlessness and selfishness of others; our own ill-will, weakness, thoughtless- ness and selfishness does harm to others; and we all suffer both as victims and villains. Apart from moral suffering there are the seem- ingly arbitrary evils of trauma, disease, old age, dying, hunger, exposure, flood, drought, and the inhuman movements of earthly elements. Suffering from natural disaster often complicates our moral lives, bringing out the worst moral suffering as well as the greatest heroism. Furthermore, much suffering is unjustly dis- tributed: one of the most desperate uses of power and domination is to push the burden of suffering off, onto those who lack the power to push it back; the poor and oppressed suffer more than they deserve. With regard to our own actions, we sometimes shrink from taking full responsibility because that exposes us to the suffering of our own guilt, and so we dehumanize ourselves by making excuses, often thereby increasing many people’s suf- fering. In the face of suffering we may come to see ourselves as victims, and because of that suffer all the more. Christianity no less than any other religious tradition has had to respond to the breadth and depth of suffering.